Muslims and global justice - Naʻīm, ʻAbd Allāh Aḥmad (Pennsylvania studies in human rights, 2011)
Encompassing more than two decades of An-Na'im's work on critical issues, Muslims and Global Justice offers a much-needed theoretical approach to the challenge of realizing global justice in a world of profound religious and cultural difference